Recognizing Factors Influencing Viral Marketing Success fromThe Standpoint of Iranian Clients. - souri, F. (The journal of contemporary issues in business and government, 2021)
Context and Purpose: Although viral marketing research is relatively considerable and also qualitative, But most of them focus mainly on the different constituentof viral marketing And less research in Iran has identified the factors that influence the position of this type of marketing; Therefore, the purpose of the present study is to identify the factors that influence viral marketing success. Analysis method: The study population included all Tehran internet clients in the first half of 1398(second half of 2019). Data were collected through field research using a simple randomized questionnaire among 398 people during the period of July 2019 to the end of August 2019. Descriptive and inferential statistics were used to analyze the conceptual model of research using SPSS software. Results: The results of the analysis of the research hypotheses showed that the rational effect of the message can confirm the success of viral marketing.